Optimization of Lead Time in Jewellery Manufacturing: Differentiation in Design and Model - Stephen Welldhies (Multidisciplinary Journal of Akseprin Indonesia, 2024)
One of the qualities that a firm must possess is the capability to launch new models more rapidly than its competitors. It will provide the organization with the potential to seize market share. However, the corporation must rapidly initiate mass production of the new models following the prototype's market introduction. Gradual mass production will provide competitors the opportunity to replicate the prototype, enabling them to seize market share if they can achieve faster production rates. This issue occurs in jewelry companies in Indonesia, namely at XYZ Company. Prototype models from XYZ Company are extensively replicated by competitors with expedited manufacturing timelines. To address this issue, the organization must analyze the fundamental reason for the sluggish mass production process. This analysis enables the formulation of recommendations for the company to enhance the production process, hence preventing market loss. A root cause analysis was performed utilizing a fishbone diagram in a case study at XYZ firm. The analysis reveals that the primary cause of the prolonged manufacturing time is the insufficient human resources engaged in the production process. In light of this conclusion, initiatives such as recruiting extra personnel and instituting overtime for employees may be implemented to expedite production time and enhance capacity.